Not fade away [videorecording (DVD)] - Van Zandt, Steve (Paramount, 2013)
From David Chase, creator of The Sopranos, comes a story about discovering your passions, following your dreams, and finding yourself. It's the 1960s and rock n' roll is changing the world. Inspired by a bold new era and his success in a local band, Douglas drops out of college to pursue his musical dreams, only to discover the harsh realities of the music industry. Douglas is forced to choose between listening to his father or listening to his heart.